1989
DOI: 10.1037/0022-3514.56.5.691
|View full text |Cite
|
Sign up to set email alerts
|

Test of a subtractive theory of "fair" allocations.

Abstract: The authors would like to express appreciation to Michael Birnbaum, Jerome Busemeyer, and Richard Harris for valuable comments or discussions, to Karen Biagini for help with data collection, and to Norman Anderson for providing his data for reanalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…When the monotonic J is linear, then the factorial plot of the I A ¥ I B effect should be parallel across the low through high levels of O A . Statistically, therefore, only the three main effects of O A , I A , and I B should be significant in ANOVA (Mellers & Hartka, 1989;Singh, 1995). This prediction follows because of the adding and subtracting operations among the three experimentally manipulated factors of O A , I A , and I B in the allocation task.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…When the monotonic J is linear, then the factorial plot of the I A ¥ I B effect should be parallel across the low through high levels of O A . Statistically, therefore, only the three main effects of O A , I A , and I B should be significant in ANOVA (Mellers & Hartka, 1989;Singh, 1995). This prediction follows because of the adding and subtracting operations among the three experimentally manipulated factors of O A , I A , and I B in the allocation task.…”
Section: Discussionmentioning
confidence: 87%
“…Towards this end, we employed a three-factor task of deciding 'fair' pay for person B (O B ) after knowing the pay of person A (O A ), input of person A (I A ), and input of person B (I B ). Singh (1995) found that the majority of Indian adults considered the differences between subjective values of inputs, relative to the pay of the comparison person, in allocating 'fair' pay as the subtractive model, in fact, prescribed (Mellers & Hartka, 1989). However, the allocation behavior was adjusted because of the 'floor' effect at the lower end and the 'ceiling' effect at the upper end of the outcome scale.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…That particular transformation has long been used with sigmoidal data (Cochran, 1940), because the arcsin has little effect on intermediate values but stretches out the ends of the scale. Specifying the transformation in advance is a more definitive statement, one justified by Mellers and Hartka's (1989) account of the distortion induced by the response scale. If this hypothetical operation had been able to make the transformed means plot in accord with the parallel pattern called for by the model, subsequent research in which tasks in which respondents make similar judgments are used (e.g., Singh, 1995) might fruitfully apply the same transformation.…”
Section: Choosing a Transformationmentioning
confidence: 99%